O tráfico de drogas na implicação das trajetórias geográficas de homens em situação de reclusão na Penitenciária Estadual de Ponta Grossa, PR - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2022)
This thesis has as a guiding question: How are the geographic trajectories of men convicted of drug trafficking instituted in the State Penitentiary of Ponta Grossa, PR (PEPG-PR)? To answer it, we conducted 18 interviews with men serving time in closed regime in the PEPG, sentenced for articles related to drug trafficking present in Law 11.343/06. To make possible the systematization and analysis of these interviews, we proposed an adaptation to Content Analysis methodology. As a result, with the transcription of the audio, we classified the excerpts of speeches, also called evocations, into discursive categories and spatialities, which relate to the periods of life corresponding to the trajectories of the interviewees. From these evocations, we understand that these subjects have their trajectories marked by the condition of being men who, besides the facet of masculinity, are also mostly poor, young, and with a low level of schooling. These markers does not can be seen in isolation, but from their intersections, which relate directly to axes of inequality, which can intensify or mitigate their positions of center or margin in the spatialities they compose. We understand that drug trafficking, in this sense, constitutes a spatiality composed from a limited range of possibilities for the existence of these subjects that, for being always open and porous, resulting from interrelationships, multiple and constantly under construction, also collaborates to the abjection of their bodies. What we explore in this reflection seeks, through the correlation between the theoretical, empirical and methodological ballast, to contribute to the enrichment of the specific field of geographic knowledge, as well as to the discussions interested in rethinking public policies in Brazil related to the problem presented.
Keywords: Espacialidades; Masculinidades; Interseccionalidade; Trajetórias de Vida; Tráfico de Drogas; Spatialities; Masculinities; Intersectionality; Life Trajectories; Drugs Traffick; CNPQ::CIENCIAS HUMANAS::GEOGRAFIA